Poverty reduction strategy papers in Latin America: The case of Bolivia - Michael Krakowski (Hamburg Institute of International Economics (HWWA), 2003)
The international development debate has undergone significant changes during the last decade. The so-called Washington consensus, often described as a focus on macroeconomic adjustment and stabilization policies, has been extended to include a new approach of institution building. Although most developing economies in fact did quite well in terms of macroeconomic stabilization, progress on poverty reduction was judged to be disappointing. The Eighties left a legacy of high levels of indebtedness, and throughout the Nineties one international initiative after another tried to resolve or at least alleviate this problem. When developing countries and international financial institutions agreed on economic policy reforms in the context of loan agreements, it was often felt that the governments lacked real commitment, which was explained by their lack of "ownership." One of the new instruments to have emerged from the international policy debate is the Poverty Reduction Strategy Paper. This new instrument pursues three objectives: (1) Poverty Reduction Strategy Papers must be drawn up by the governments concerned in a participatory process, intended to assure national consensus and ownership. (2) It is hoped that the explicit focus on poverty reduction will improve results in this area. (3) And if the international community accepts a country's PRSP, a high percentage of outstanding debt will be written off by bilateral and multilateral donors within the HIPC (highly indebted poor countries) initiative...
Keywords: 330